2022
DOI: 10.1002/celc.202200245
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Role of the Supporting Electrode for Creating Heterogeneity in Single Entity Electrochemistry

Abstract: Single entity electrochemistry experiments are typically motivated by the need to reveal how heterogeneity affects performance within inherently diverse nanoparticle populations. Here we show that a commonly used supporting electrode, tin‐doped indium oxide (ITO), can also play a significant role in creating heterogeneity in nanoparticle electrochemical responses. To investigate the impact of the substrate, we optically monitored the electrodissolution kinetics of gold nanoparticles on ITO thin films with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…A similar behavior has been recently evidenced for the competition between ITO reduction reaction and hydrogen nanobubbles nucleation at the very same ITO electrodes [59] or from the nanoscale imaging of the heterogeneous electrochemical activity of ITO surfaces. [62][63][64]…”
Section: Chemical Composition Of Npsmentioning
confidence: 99%
“…A similar behavior has been recently evidenced for the competition between ITO reduction reaction and hydrogen nanobubbles nucleation at the very same ITO electrodes [59] or from the nanoscale imaging of the heterogeneous electrochemical activity of ITO surfaces. [62][63][64]…”
Section: Chemical Composition Of Npsmentioning
confidence: 99%
“…9,11,39,57,58 Because this experiment directly compares the DFS and PL responses for the same particles, differences between AuNRs caused by heterogeneity in size, shape, and electrical contact with the ITO electrode discussed recently by Willets and co-workers are avoided. 59 At lower energies, the single-particle PL spectrum follows the DFS spectrum (Figure 2A). This result is consistent with previous work which showed that the plasmon serves as an antenna for AuNR emission.…”
mentioning
confidence: 78%
“… normalΔ Q sca ( N ) = Q sca ( N + Δ N ) Q sca ( N ) Q sca ( N ) Using the average Δ N at positive potentials, the DFS is predicted to decrease by 6%, consistent with the average experimental decrease of 11 ± 5%. The small differences between calculated and measured results can be attributed to heterogeneity in particle size and variability in contact with the ITO substrate. , Thus, the modulation of charge density fully describes the changes in the scattering intensity shown in the top panel of Figure B.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The change in M is also accompanied by a drop in the integrated scattering intensity of the o || (Figure 2F), allowing us to monitor the kinetics of the chemidissolution process and indicating that the particle decreases in size during the dissolution process, consistent with previous reports. 23,38,39 Interestingly, by fitting the o || to a twodimensional Gaussian and extracting the peak position, we observe a directional change in the center-of-mass over time (Figure 2G). If the NR was dissolving from each end at equal rates, we would expect the center-of-mass to remain unchanged during chemidissolution, even as the particle changed from rod-like to sphere-like (Figure S5A).…”
mentioning
confidence: 96%